Multi‐site nerve block catheters for postoperative analgesia in extended scapulectomy and free‐flap reconstruction. Issue 2 (14th October 2022) - Cowgill, A. E.; Womack, J.; Powell, L.
Summary: Scapulectomy is performed as a limb‐sparing procedure in the management of tumours of the proximal humerus and shoulder girdle. Analgesic outcomes following this procedure are poorly documented in the literature. In our case, satisfactory analgesia following extended scapulectomy and free‐flap reconstruction was achieved with a combination of multi‐site continuous nerve block catheters and patient‐controlled analgesia, for a patient with chronic pain who had a high pre‐operative opioid requirement. Multiple continuous nerve block catheters were used, including interscalene and paravertebral catheters to provide analgesia for the shoulder resection, with a fascia iliaca compartment catheter providing analgesia to free‐flap donor site on the the anterolateral thigh. These continuous nerve block catheters contributed to effective postoperative analgesia and low postoperative intravenous opioid requirements in this case.